Associations of five blood heavy metals with hepatitis B virus infection and immunity in adults: a cross-sectional study - Xinpeng Li; Lei Bi; Lu Han (BMC, 2024)
Abstract Background Heavy metal pollution has emerged as a significant concern for human health, prompting increased awareness of its potential adverse effects. While previous research has established a connection between heavy metals and liver function biomarkers, the specific relationship between heavy metals and HBV infection remains unexplored. This cross-sectional study aims to investigate the potential correlations between five blood heavy metals - lead, cadmium, mercury, manganese, and selenium - and the presence of HBsAg, HBsAb, and HBcAb in adults. Methods The study utilized data from NHANES 2007-2018. Participants were classified into four groups based on their infectious status, and the association between heavy metals and HBV infection was analyzed using multiple logistic regression and stratification analysis. Results A total of 8431 participants were included, with 5 436 classified as Susceptible, 1 765 as Vaccinated, 865 as Natural Infection, and 103 as Acute/Chronic HBV Infection. The Vaccinated group exhibited a lower mean age (34.52 ± 14.16 years) compared to the other groups. Statistically significant differences in heavy metal concentrations (except selenium) were observed among the groups (P < 0.001). After adjusting for covariates, lead was significantly associated with HBV infection (Q2: OR 2.37, 95%CI 1.04-5.39; Q3: OR 2.34, 95%CI 1.01-5.40), and positive trends were observed for high blood concentrations of mercury (Q4: OR 3.03, 95%CI 1.31-7.04) and manganese (Q4: OR 2.52, 95%CI 1.20-5.28). Furtherly, the presence of lead reduced the protection of HBsAb (Q2: OR 0.84, 95%CI 0.73-0.97; Q3: OR 0.77, 95%CI 0.66-0.90; Q4: OR 0.83, 95%CI 0.70-0.98). Subgroup analysis indicated that cadmium was associated with an increased risk of HBV infection in Asians (OR 1.36, 95%CI 1.03-1.78) and individuals with a BMI range of 25 to 30 (OR 1.60, 95%CI 1.17-2.18). Conclusions The study's findings suggest a correlation between elevated blood Pb concentrations and reduced immunization rates against hepatitis B. Individuals with a positive HBsAg exhibit lower blood Se concentrations and higher blood Hg and Mn concentrations.